Pengaruh Modal, Pengalaman Usaha, Strategi Promosi, dan Pendidikan Terhadap Keuntungan Pelaku UMKM Fashion pada Marketplace Online di Kota Semarang - Henrico Victor Parluhutan; Achma Hendra Setiawan (Universitas Diponegoro, 2020)
The 4.0 industrial revolution brought a profound impact on the economic sector. Interner is one of the factors in technological progress that causes disruption in the field of trade where trading is shifting from offline to online. The research aims to analyze the effect of capital, business experience, promotion strategies and education on the profit of fashion SMEs in the online marketplace in the city of Semarang. The population in this study are fashion SMEs in Semarang City who sell at online marketplace Tokopedia, Bukalapak, Shopee, Lazada and Blibli.com with a total sample of 96 respondents taken by accidental sampling and analyzed using multiple linear regression (OLS). The independent variables are capital, business experience, promotion strategies, and education, while the dependent variable in this study is the profit of fashion SMEs. The results showed that the capital variable had a positive and significant effect with a coefficient of 1.80 and a probability value of 0.00, a promotion strategy had a positive and significant effect with a coefficient of 77.16 and a probability value of 0.00 and education had a positive and significant effect on profits. fashion SMEs practitioners with a coefficient value of 27.3 and probability value of 0.00. While the business experience variable does not affect the profit of fashion MSME entrepreneurs who sell on the online marketplace.